Perceived Fairness, Emotions, and Intention of Fast Food Chain Restaurants Customers in Indonesia - Hety Budiyanti; Shine Pintor Siolemba Patiro (Gadjah Mada International Journal of Business, 2018)
This study aims to investigate interrelationships among perceived service fairness, emotions, and behavioral intentions in a fast food chain restaurant context. we use terms that are commonly use on the study of fairness or justice perception. This study uses purposive sampling and the survey method to generate our sample which consists of 800 respondents from big cities in Indonesia, namely: Jakarta, Semarang, Surabaya, Medan, and Makassar. The data are analyzed using Structural Equation Modeling (SEM). The results show different roles for each fairness perception in relation to peoples’ emotions and behavioral intentions, based on the Mehrabian-Russel model. Three fairness variables (price fairness, outcome fairness and interactional fairness) have positive and significant effects on customers’ positive emotions, while, procedural fairness does not influence the formation of a positive emotion. Furthermore, a positive emotion has a positive influence on a customer’s behavioral intention. Data collected in this study are limited to the context of the restaurant industry, therefore, precaution must be taken when generalizing these results to other industries. The results of this study can serve as guidelines for managers in the restaurant industry to develop effective and efficient strategies for ensuring their services’ perceived fairness and its impact on both customers’ retention rates and the companies’ financial gains.